METAFORA SEKSUALITAS DALAM KOLOM KOMENTAR INSTAGRAM: ANALISIS METAFORA KRITIS - Wilda Khairani; Arie Andhiko Aji (PRASASTI: Journal of Linguistics, 2022)
Metaphors are generally used as a way to construct an abstract or difficult-to-understand concept in a human's mind. However, the metaphor of sexuality tends to disguise or cover one thing with another. This phenomenon is easily found in the comment section of women's Instagram account. This research combined the semantic and pragmatic perspectives in critical metaphor analysis and implemented qualitative methods to reveal the language attitudes and social elements that underlie the metaphor of sexuality. The research questions are (1) how is the conceptual mapping between the source and target domain of sexuality metaphors, (2) what types of metaphors are found, and (3) how are language attitudes and social elements that trigger the production of metaphors. The results showed that metaphors are widely used to refer to female breasts as inanimate objects. On the other hand, men's sex organs, men's thoughts, and men's gazes are described as animate objects. This shows how women on social media are seen as objects that can trigger and satisfy men's desires.